Influence of different work and rest distributions on performance and fatigue during simulated team handball match play - Moss, S. L.; Twist, C. (The Journal of Strength and Conditioning Research, 2015)
This study investigated the effect of different interchange strategies on performance and pacing strategy during a simulated team-sport protocol. Eight youth male team handball players completed 2 conditions (LONG—work: 3 × 13:00 minutes, rest: 8:00 minutes; SHORT—work: 5 × 7:48 minutes, rest: 3:45 minutes). Participants were tested for 20-m sprint, countermovement jump, throwing performance, and heart rate (HR) during conditions. Postcondition measures included repeated shuttle-sprint and jump ability, session rating of perceived exertion, blood lactate, and glucose. Faster sprint (3.87 ± 0.27 seconds cf. 3.97 ± 0.24 seconds, effect size [ES] = 0.39, p = 0.03) and throwing performance (70.02 ± 7.40 km/h cf. 69.04 ± 5.57 km/h, p > 0.05, ES = -0.15) occurred in SHORT compared with LONG by a "likely small" difference. Higher summated HR (157 ± 21 cf. 150 ± 15 AU) occurred in SHORT compared with LONG by a "likely small" difference (ES = 0.37, p > 0.05). SHORT resulted in lower session rating of perceived exertion (224 ± 45 AU cf. 282 ± 35 AU, ES = 1.45, p = 0.001) and higher blood glucose (6.06 ± 0.69 mmol/l cf. 4.98 ± 1.10 mmol/l, ES = -1.17, p = 0.03) by a "most likely moderate" difference compared with LONG. Repeated shuttle sprint was better preserved after SHORT, with "moderately lower" 10 and 25 m times (p = 0.05). Interchange strategies using SHORT rather than LONG work and rest periods result in lower physiological load, leading to improved fatigue resistance and better preservation of high-intensity movements during matches.